Overlap between Fibular Aplasia, Tibial Campomelia, and Oligosyndactyly and Fuhrmann's Syndromes in an Egyptian Female Infant - Abdalla, Ebtesam M.; El-Beheiry, Ahmed A. (Journal of Pediatric Genetics, 2017)
We report a rare congenital limb defect with combined features of both fibular aplasia, tibial campomelia, and oligosyndactyly (FATCO) and Fuhrmann's syndromes. A female newborn infant, born to nonconsanguineous Egyptian parents, presented with isolated abnormalities of the lower limbs comprising bilateral shortening and anterior bowing of the lower limbs at the distal third of the tibia and split foot. Radiographic examination revealed complete absence of both fibulae, anterolateral bowing and shortening of the tibia, bowing of the femora, and absence of several metatarsal and phalangeal bones. The upper limbs were clinically and radiologically normal, and the infant had neither facial dysmorphism nor other associated visceral anomalies. The presented case highlights an extremely rare limb deficiency syndrome, and together with additional case reports, it could be useful to further delineate this condition.
Keywords: FATCO; Fuhrmann's syndrome; fibular aplasia; tibial campomelia; oligosyndactyly